2005
DOI: 10.1007/s11095-005-5279-3
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Cross-Linked Polyvinylpyrrolidone as a Spheronization Aid: A Promising Alternative to Microcrystalline Cellulose

Abstract: Crospovidone can be successfully employed as a spheronization aid to produce good pellets without the need of a binder, unlike most of the previously proposed materials. This study exemplified the enormous potential of crospovidone to serve as a competent alternative to MCC in the production of pellets by extrusion-spheronization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…This meant that MCC grades with a larger W 710 μm value and smaller SSA tend to generate a smaller Torque max . The relationship between packing abilities of MCC powders (bulk and tapped densities) and wet mass consistency has been well established and explained (3)(4)(5)(6). Variables which had very large error bars (confidence intervals) spanning the positive and negative regions were not deemed to have significant effects.…”
Section: Wet Massing Behavior Determined Using Mixer Torque Rheometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This meant that MCC grades with a larger W 710 μm value and smaller SSA tend to generate a smaller Torque max . The relationship between packing abilities of MCC powders (bulk and tapped densities) and wet mass consistency has been well established and explained (3)(4)(5)(6). Variables which had very large error bars (confidence intervals) spanning the positive and negative regions were not deemed to have significant effects.…”
Section: Wet Massing Behavior Determined Using Mixer Torque Rheometrymentioning
confidence: 99%
“…From the encouraging performance of crospovidone to aid in extrusion-spheronization, Liew et al (3) concluded that for any given material to serve as a competent spheronization aid, the internal water repository has to possess adequate capacity and rigidity to modulate the amount of water released under pressure for lubrication during extrusion. While many previously proposed materials have the ability to absorb water, these materials lacked the rigidity and binding ability (of MCC) to regulate water distribution by coping with the pressures exerted during extrusion-spheronization.…”
Section: Introductionmentioning
confidence: 99%
“…A socalled spheronization aid is generally needed to provide the moistened bulk (paste) with the above-stated rheological properties (5). In this respect, microcrystalline cellulose (MCC) is widely regarded as a key excipient due to its potential for retaining large amounts of moistening liquid that imparts binding, lubricating and plasticizing properties to the mass (1,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Crospovidone is a synthetic, cross-linked homopolymer of N-vinyl-2-pyrrolidone that is free flowing and nonirritating [10][11][12]. Although the linear poly(vinylpyrrolidone) is water soluble, cross-linking leads to the hydrophilic, but water-insoluble, crospovidone.…”
Section: Introductionmentioning
confidence: 99%
“…Polyplasdone ® is the product name for a family of crospovidone products available from International Specialty Products (now Ashland Specialty Ingredients). The totally synthetic production of crospovidone minimizes lot-tolot variability observed with MCC [11]. A well-characterized polymer that is considered biocompatible and nontoxic, crospovidone is generally regarded as safe for use in oral dosage forms administered to humans.…”
Section: Introductionmentioning
confidence: 99%